Pericarditis Caused by Enterococcus faecium with Acute Liver Failure Treated by a Multifaceted Approach including Antimicrobials and Hemoadsorption - Thomas Köhler; Mathias W. Pletz; Simon Altmann; Carmen Kirchner; Elke Schwier; Dietrich Henzler; Günther Winde; Claas Eickmeyer (Case Reports in Critical Care)
Background. Sepsis and septic shock are still life-threatening diseases with a high mortality rate. We report a complex case of peritonitis with pericarditis and acute liver failure caused by septic shock. Potentially hepatotoxic antibiotic therapy levels were monitored using the liver maximum capacity (LiMAx®) test, and standard treatment was supplemented by adjunctive hemoadsorption with CytoSorb®. Case Presentation. The case features a 29-year-old woman with a history of Crohn’s disease and cachexia. Peritonitis caused by Enterococcus faecium was diagnosed later due to an ileum perforation. The hematogenic spread led to pericarditis. In addition, sepsis-related acute liver failure complicated antimicrobial therapy further. The combination of standard therapy, anti-infective medication, and blood purification was associated with inflammation control, hemodynamic stabilization, and a concomitant decrease in vasopressor support. An efficient, sustained reduction in plasma bilirubin levels was achieved while maintaining liver function. Conclusions. This case shows how complex infectious diseases with an atypical infectious focus resulting in septic shock can be successfully treated. A combination of antimicrobial (tigecycline and caspofungin) and long-term adjunctive hemoadsorption therapy was administered while hepatotoxic antibiotic medication was monitored by liver function testing.